Synergic carcinostatic effects of ascorbic acid and hyperthermia on Ehrlich ascites tumor cell - Saitoh, Y.; Yoshimoto, T.; Kato, S.; Miwa, N. (Experimental Oncology, 2015)
Aim: In this study, we evaluated the carcinostatic effects of combined ascorbic acid (AsA) and a capacitive-resistive electric transfer (CRet) hyperthermic apparatus-induced hyperthermic treatment on Ehrlich ascites tumor (EAT) cells. Materials and Methods: EAT cells were exposed to various AsA (0–10 mM) concentrations for 1 h; they subsequently underwent CRet treatment for 15 min at 42 °C. Cell viability was assessed by the WST-8 assay 24 h after the combined treatment. Reactive oxygen species involvement was evaluated using catalase and tempol; caspase-3/7 activation was determined by their fluorescent substrates; cell proliferation were estimated by time-lapse observation. The effect on the cell cycle was analyzed by flow cytometry. Results: Combined AsA and CRet treatment synergistically suppressed cell viability compared with either treatment alone, and these synergistically carcinostatic effects were evident even at noncytotoxic concentrations of AsA alone (≤ 2 mM). The carcinostatic effects of combined AsA and CRet treatment were attenuated in a dose-dependent manner by catalase addition, but not by the superoxide anion radical scavenger tempol. Time-lapse observation revealed that combined AsA and CRet treatment activated caspase-3/7 at 10–24 h after treatment, accompanied by significant cell growth suppression. Cell cycle analysis revealed that the rate of sub-G1-phase (apoptotic) cells was drastically increased at 12 h and 24 h, and that the G2/M-phase cells gradually increased at 6–24 h after treatment. Conclusion: These results indicate that combined AsA and CRet treatment synergistically inhibits EAT cell growth through G2/M arrest and apoptosis induction via H₂O₂ generation at lower AsA concentrations; this carcinostatic effect cannot be exerted by AsA alone. Key Words: L-ascorbic acid, CRet system, hyperthermic action, Ehrlich ascites tumor cell, carcinostatic effect.